Synthesis, Analysis, and Photocatalysis of Mg-Doped ZnO Nanoparticles - S. Sa-nguanprang (2020)
© 2019, Pleiades Publishing, Ltd. Abstract: Mg-doped ZnO nanoparticles with different contents of Mg dopant have been synthesized by tartaric acid complex method with subsequent calcination at 600°C for 2 h. The products have been characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), Fourier transform infrared spectroscopy (FTIR), Raman spectroscopy, and X-ray photoelectron spectroscopy (XPS). The analytical results have revealed the presence of wurtzite ZnO with hexagonal structure for undoped and Mg-doped samples with particle sizes of 100–200 nm for ZnO and 30–70 nm for 5 wt % Mg-doped ZnO. Visible light driven photocatalytic properties of ZnO and Mg-doped ZnO have been monitored through photodegradation of methylene blue (MB) identified by liquid chromatography-mass spectrometry (LC–MS). In this research, 5 wt % Mg-doped ZnO have shown the highest photocatalytic activity of 99% within 60 min.